Factors affecting the adoption of chatbots in the South African financial services context - Kedijang, Seolebaleng Priscilla (University of the Witwatersrand, Johannesburg, 2023)
This research focuses on the factors that affect the adoption of chatbots in the South African financial services industry. It explores the direct and indirect influences of the constructs of the Unified Theory of Acceptance and Use of Technology (UTAUT), the attitude construct from Technology Acceptance Model (TAM), self-efficacy, as well as security-related construct. The study used a cross-sectional, quantitative research methodology, and data was collected through self-administered online questionnaires. Data analysis included correlation and regression analysis, factor reduction, exploratory factor analysis, mediation, and moderation analysis. The research constructs were tested for direct and indirect effects, additionally, gender, age, and previous chatbot experience was used to moderate the behavioural intention relationships in the conceptual framework. The findings indicate that facilitating conditions, attitude, perceived risk, effort expectancy, utilitarian performance expectancy, perceived security, perceived trust, SI, and hedonic performance expectancy have an indirect or direct effect on chatbot adoption in South Africa. However, self-efficacy proved to be an insignificant construct in the research model. In the wake of the digital revolution, the current state of chatbot usage in South Africa seems to be growing with more service providers already having implemented chatbots into their businesses
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business Schooly, University of the Witwatersrand, Johannesburg, 2023
Keywords: Chatbot; Technology adoption; Financial services; UCTD; SDG-9: Industry, innovation and infrastructure